HUKUM ISLAM: ANTARA SUPERIOR DAN INFERIOR DALAM PENEGAKAN HUKUM DI INDONESIA - Ali, Lukman (DIKTUM: Jurnal Syariah dan Hukum, 2015)
This paper examines the view of Islamic law on the superior and inferior in law enforcement in Indonesia. The focus of the problem is how the concept and the factors that affect law enforcement and a review of the enforcement of Islamic law in Indonesia. This study concluded that law enforcement is an effort being made to make the law, both in the formal sense narrow or broad in the sense of material, as a code of conduct in any legal act performed by all elements of society. While the law enforcement process is influenced by five factors: (1) factors laws or regulations, (2) factors of law enforcement officers, (3) factors means or facilities, (4) community factors, and (5) cultural factors. Basically, Islamic law believes that the goal or purpose of the law is the law of justice. Therefore, Islamic law does not require the existence of discrimination or superior - inferior before the law. Everyone is equal before the law.